2010
DOI: 10.14314/polimery.2010.055
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen fluxes of vegetable origin

Abstract: Bitumen fluxes of vegetable origin Summary-Methods of preparation of bitumen fluxes from rapeseed and linseed oil methyl esters were developed. The methods consist in the catalytic oxidation of vegetable oil methyl esters in the absence or presence of peroxides as the accelerators. The products obtained can be used as environmentally friendly bitumen fluxes. The rapeseed oil methyl ester has to be oxidized at elevated temperature in the presence of a catalyst. Linseed oil methyl ester does not need pre-oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The new generation of binders constitute mixtures of asphalt and vegetable oil or its derivatives in the form of methyl esters [ 10 ]. During the execution of the process, it is possible that their activation determines the usability of these vegetal resources as components of asphalts.…”
Section: Materials Used In Lab Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new generation of binders constitute mixtures of asphalt and vegetable oil or its derivatives in the form of methyl esters [ 10 ]. During the execution of the process, it is possible that their activation determines the usability of these vegetal resources as components of asphalts.…”
Section: Materials Used In Lab Testsmentioning
confidence: 99%
“…The required quality of the RAP can be reached through the control of its homogeneity. The moisture content of RAP is an important issue [ 10 , 11 , 12 , 13 ]. The higher the percentage content of RAP and its moisture content, the higher the temperature required for the aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Bitumen preparations where the viscosity of the binder has been reduced by the addition of relatively non-volatile oils are referred to as fluxed bitumens. The added oil is known as a fluxing agent or fluxant that is typically gas oil, vegetable based oils [5,10], or methyl esters of fatty acids [13,16].…”
Section: Introduction To Bitumen Fluxingmentioning
confidence: 99%
“…Previous studies have shown that the liquid products obtained from oxidation of rapeseed oil methyl esters can be used as a bitumen flux [ 27 , 28 ]. Fluxed road bitumen containing this oxidation product increased its consistency over time, had a high ignition temperature, and displayed satisfactory adhesion to the aggregate.…”
Section: Introductionmentioning
confidence: 99%